Evaluation of Serbian black locust honey quality parameters as a contribution to confirmation of its botanical origin. (September 2019) - Vranic, D; Petronijevic, R; Koricanac, V; Djinovic Stojanovic, J; Lilic, S; Borovic, B; Lukic, M
Abstract: Acacia honey, like many other specialized kinds of honey, is derived purely from one plant species, in this case, the nectar of black locust ( Robinia pseudoacacia ) tree flowers. The present study investigated the quality of 270 acacia honeys from the Serbian market, collected during 2017 and 2018. Chemical and physical properties of honey were evaluated according to Serbian regulation. All applied methods were performed according to the Harmonized Methods of the International Honey Commission. Summarizing the results presented, none of the tested acacia honeys exceeded limits of national or EU regulations for moisture, free acid and insoluble matter contents as well as electrical conductivity. However, the most common parameters for non-compliant honeys were hydroxymethylfurfural and sugar contents and diastase activity. Among these parameters, this study shows the fructose to glucose ratio is also an important quality factor, significant for confirming the origin of acacia honey, while the correlation between glycemic index and the fructose to glucose ratio is especially important for individual honey consumers with impaired glucose tolerance or insulin resistance.